2019
DOI: 10.1021/acsami.9b06560
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed Water-Insertable Layered Oxides with Synergistic Effect of Transition-Metal Elements for High-Performance Oxygen Evolution Reaction

Abstract: Oxygen evolution reaction (OER) is a key step in many energy conversion and storage processes. Here, by rationally adding an appropriate amount of Mn into the lattice of a layered Na x CoO 2 parent oxide, high solubility of iron into the Na x CoO 2 oxide lattice is realized without the use of an extremely air-sensitive Na 2 O 2 raw material, and the synergy created between the Co and Fe can boost the catalytic activity of the layered oxide for OER. Moreover, the water intercalation capability of the layered ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…On the other hand, the P atoms carries more positive charge, making it easier to adsorb OH. It has been reported that the synergistic effect between atoms can promote charge transfer and accelerate the catalytic reaction [ 67 , 75 , 76 ]. Therefore, the synergistic action of P and Ni atoms can promote the charge transfer between atoms, and makes P atoms the active sites in OER.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the P atoms carries more positive charge, making it easier to adsorb OH. It has been reported that the synergistic effect between atoms can promote charge transfer and accelerate the catalytic reaction [ 67 , 75 , 76 ]. Therefore, the synergistic action of P and Ni atoms can promote the charge transfer between atoms, and makes P atoms the active sites in OER.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, multimetal oxide is also favorable to enhance catalytic activity because the diversity of metal compositions can offer more possible approaches to design catalysts . The synergy between different components can adjust the electronic structure to achieve ideal adsorption/desorption sites to enhance the catalytic activity for OER and/or HER. , Cui et al prepared ultrasmall NiFeO x nanoparticles for OWS through lithium-induced conversion, which can attain 10 mA cm –2 at 1.51 V . Wei et al fabricated CoFe 2 O 4 nanosheets via surface-defect engineering strategy, which exhibited excellent OWS activity with 1.53 V to reach 10 mA cm –2 .…”
Section: Introductionmentioning
confidence: 99%
“…18 The synergy between different components can adjust the electronic structure to achieve ideal adsorption/desorption sites to enhance the catalytic activity for OER and/or HER. 19,20 Cui et al prepared ultrasmall NiFeO x nanoparticles for OWS through lithium-induced conversion, which can attain 10 mA cm −2 at 1.51 V. 21 nanosheets via surface-defect engineering strategy, which exhibited excellent OWS activity with 1.53 V to reach 10 mA cm −2 . 22 Although these works exhibited highly efficient catalytic activity for water electrolysis, they only focus on small current density.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Particularly, first-row transition metal-based materials, such as oxyhydroxides, oxides (e.g., spinel oxides and perovskite oxides), and metal phosphides/chalcogenides reportedly show outstanding OER performance, given their flexible electronic structure and enriched active sites [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Notably, the electrocatalytic activities of many reported compounds based on nonprecious transition metals are even superior to those of noble-metal-based catalysts [ 23 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%